Foundations of Classical Physics - Bates, Simon (The University of Hull)
A complete course in classical physics, contributed by the School of Physics and Astronomy at the University of Edinburgh as part of the UKOER Skills for Scientists project. The material covers introductory kinematics, dynamics, statics and oscillations.